The Reversed Implementation of the ICC’s Principle of Complementarity: Case Study of Argentina Investigation for Rohingyas - Diajeng Wulan Christianti; Chloryne Trie Isana Dewi; Christyanti, B. Lora (Padjadjaran Journal of International Law, 2023)
Complementarity is the basic principle of the ICC’s jurisdiction. As a fundamental principle, it harmonizes the relationship between ICC and National Courts. The Rome Statute clearly states that the ICC is complementary to national courts. However, in the case of Rohingya, the Argentine Lower Court applied this principle in reverse by rejecting the investigation, requested by the Burmese Rohingya Organization UK under universal jurisdiction, for the case of Rohingya since the ICC had already investigated a similar case. This paper seeks to answer whether the ICC’s complementarity principle can be applied in reverse, as decided by the Argentine Lower Court, according to international law. A juridical normative research method will be used to address these issues. In addition, the recognized principles of interpretation in international law will be used to enrich the meaning of the ICC’s complementarity. Based on the analysis, it is obvious that, according to international law, the complementarity cannot be applied in reverse, even by states parties to the Rome Statute. According to the Rome Statute's provisions, every State is required to exercise criminal jurisdiction over persons responsible for international crimes. For this reason, this paper strengthens the arguments for the Argentine Appeal Court to overturn the Lower Court’s decision and reopen the investigation into the case.